Water-limiting conditions alter the structure and biofilm-forming ability of bacterial multispecies communities in the alfalfa rhizosphere - Bogino, Pablo Cesar (2013)
Biofilms are microbial communities that adhere to biotic or abiotic surfaces and are enclosed in a protective matrix of extracellular compounds. An important advantage of the biofilm lifestyle for soil bacteria (rhizobacteria) is protection against water deprivation (desiccation or osmotic effect). The rhizosphere is a crucial microhabitat for ecological, interactive, and agricultural production processes. The composition and functions of bacterial biofilms in soil microniches are poorly understood. We studied multibacterial communities established as biofilm-like structures in the rhizosphere of Medicago sativa (alfalfa) exposed to 3 experimental conditions of water limitation. The whole biofilm-forming ability (WBFA) for rhizospheric communities exposed to desiccation was higher than that of communities exposed to saline or nonstressful conditions. A culture-dependent ribotyping analysis indicated that communities exposed to desiccation or saline conditions were more diverse than those under the nonstressful condition. 16S rRNA gene sequencing of selected strains showed that the rhizospheric communities consisted primarily of members of the Actinobacteria and α- and γ-Proteobacteria, regardless of the water-limiting condition. Our findings contribute to improved understanding of the effects of environmental stress factors on plant-bacteria interaction processes and have potential application to agricultural management practices.